The hallowed precint in Bécquer and Ruskin - del Vecchio, Eugene Francis (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
A comparison of the hallowed precint in Gustavo A. Bécquer and John Ruskin can best be approached intertextually and intersubjectively. In this context Bécquer and Ruskin, who did not know each other's work, create their hallowed precints in Toledo and Venice, respectively. The hallowed precint is defined as a holy place in a person's private universe where, according to M. Eliade, he receives the revelation of a reality other than the one in which he participates through ordinary daily life. Like many other nineteenth century writers, they shared a romantic literary heritage: the influence of Byron, Chateaubriand, and Scott as well as a nostalgia for a forlorn historical past whose objective correlative is the architectural ruin. And when these medieval cities are perceived as the ideal personification of ineffable women, we have the elaboration of a hallowed precint that constitutes the affective center of their respective works.
Keywords: Gustavo Adolfo Bécquer; John Ruskin